An experimental investigation into ignition and combustion of groups of slurry fuel droplets containing high concentrations of water; Fuel Processing Technology; Vol. 210 - Valiullin T. R. Timur Radisovich; Vershinina K. Yu. Kseniya Yurievna; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2020, 2020)
Title screen